1997
DOI: 10.1021/jm9702387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Willardiine and 6-Azawillardiine Analogs:  Pharmacological Characterization on Cloned Homomeric Human AMPA and Kainate Receptor Subtypes

Abstract: Both willardiine and azawillardiine analogs (18-28) have been reported to be potent and selective agonists for either AMPA or kainate receptors. We report here the novel synthesis and pharmacological characterization of a range of willardiine (18-23) and 6-azawillardiine (24-28) analogs on cells individually expressing human homomeric hGluR1, hGluR2, hGluR4, or hGluR5 receptors. Reaction of the sodium salts of substituted uracils (7-12) or 6-azauracils (13-16) with (S)-3-[(tert-butoxycarbonyl)amino]oxetan-2-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 21 publications
5
90
0
Order By: Relevance
“…Studies performed on cortical wedges, which mainly reflect activation of the AMPA receptors, showed that the 5-ethyl analog of AMPA was more potent than AMPA, whereas the propyl and butyl analogs showed decreased potencies (Sløk et al, 1997). These observations and studies of willardiine analogs (Wong et al, 1994;Jane et al, 1997;Swanson et al, 1998) have resulted in a hypothesis proposing that the AMPA and kainate receptors might contain a hydrophobic cavity that can accommodate hydrophobic substituents to a certain size at the 5-position of the isoxazole ring of the AMPA molecule (Krogsgaard-Larsen et al, 1996).…”
mentioning
confidence: 68%
“…Studies performed on cortical wedges, which mainly reflect activation of the AMPA receptors, showed that the 5-ethyl analog of AMPA was more potent than AMPA, whereas the propyl and butyl analogs showed decreased potencies (Sløk et al, 1997). These observations and studies of willardiine analogs (Wong et al, 1994;Jane et al, 1997;Swanson et al, 1998) have resulted in a hypothesis proposing that the AMPA and kainate receptors might contain a hydrophobic cavity that can accommodate hydrophobic substituents to a certain size at the 5-position of the isoxazole ring of the AMPA molecule (Krogsgaard-Larsen et al, 1996).…”
mentioning
confidence: 68%
“…Quisqualate, aniracetam, AMPA, and CNQX were obtained from Tocris. The willardiine compounds were synthesized as described previously (41). The GluR2 S1S2J construct was obtained from Eric Gouaux (Vollum Institute; Ref.…”
Section: Methodsmentioning
confidence: 99%
“…propionic acid, (S)-5-iodowillardiine, and (4R)-isopentyl glutamate are potent agonists at homomeric GluK1 receptors but have little to no activity at GluK2 receptors (Clarke et al, 1997;Jane et al, 1997;Zhou et al, 1997;Small et al, 1998;Brehm et al, 2003;). GluK1 selectivity arises from the larger GluK1 binding cavity, which relieves steric occlusion of the bulky tert-butyl group of ATPA and halogen atom of (S)-5-iodowillardiine (Mayer, 2005).…”
Section: Glutamate Receptor Ion Channelsmentioning
confidence: 99%